Association of Hepatitis 'E' Virus With an Outbreak of Hepatitis at a Military Training Camp in Nepal - Clayson, Edward T; Vaughn, David W; Innis, Bruce L; Shrestha, Mrigendra P; Pandey, Rajiv; Malla, Devendra B (Medical Journal of Shree Birendra Hospital, 1998)
Association of Hepatitis 'E' Virus With an Outbreak of Hepatitis at a Military Training Camp in Nepal